Quantum Groupoids Acting on Semiprime Algebras - Inês Borges; Christian Lomp (Advances in Mathematical Physics)
Following Linchenko and Montgomery's arguments we show that the smash product of an involutive weak Hopf algebra and a semiprime module algebra, satisfying a polynomial identity, is semiprime.